Insect Pests of Underutilized Vegetables and Their Management: An Appraisal (Current Horticulture, 2024)
Vegetable crops that are not traded widely or economically developed on a large scale are considered underutilized. A few of  the vegetables on the list are curry leaf, drumstick, amaranthus, cherry tomato, Chinese cabbage, winged bean, and aquatic  veggies etc. Similar to more popular vegetables, these less common vegetables are also vulnerable to a variety of insect and mite  attacks over the period of their growth, which can some time cause massive destruction. This chapter describes the list of these  insect and acarine pests, their bioecology, host range, damage symptoms, and integrated management techniques in light of the  changing climatic conditions.
Keywords: Underutilized vegetables; insect and acarine pests; damage; integrates management